2021
DOI: 10.1245/s10434-021-10730-7
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Breast-Conserving Therapy for Non-Hispanic American Indian/Alaska Native Women Compared with Non-Hispanic White Women

Abstract: Background Little is known about the surgical patterns of American Indian/Alaska Native (AI/AN) breast cancer patients. The purpose of this study is to determine whether there are disparities in breast cancer surgery and radiation therapy between non-Hispanic AI/AN (NH-AI/AN) women and non-Hispanic White (NHW) women. Methods Data from the National Program of Cancer Registries of the Centers for Disease Control and Surveillance, Epidemiology, and End Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…This finding should be interpreted with caution owing to small numbers but is noteworthy considering that little is known regarding outcome disparities in this group. Prior research has shown that those who identify as American Indian/ Alaska Native experience considerable health disparities 29,30 and, specific to breast cancer, are more likely than White patients to present for treatment with advanced-stage breast cancer 31 and less likely to undergo breast-conserving surgery. 32 Future work is needed to understand the barriers to quality cancer care experienced by Indigenous people to develop mitigation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This finding should be interpreted with caution owing to small numbers but is noteworthy considering that little is known regarding outcome disparities in this group. Prior research has shown that those who identify as American Indian/ Alaska Native experience considerable health disparities 29,30 and, specific to breast cancer, are more likely than White patients to present for treatment with advanced-stage breast cancer 31 and less likely to undergo breast-conserving surgery. 32 Future work is needed to understand the barriers to quality cancer care experienced by Indigenous people to develop mitigation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…These areas contain or are located adjacent to federally recognized tribal lands 20. Approximately 62% of the AI/AN people live in PRCDA counties and race classification for AI/AN people is more accurate in these areas compared with other counties 21 Figure 1. shows the location of PRCDA counties in the United States.…”
Section: Methodsmentioning
confidence: 99%
“…American Indian and Alaska Native (AIAN) patients face significant healthcare disparities when seeking and receiving care from numerous surgical subspecialties, including bariatric, vascular, and oncologic surgery 1–3 . Furthermore, AIAN populations remain the most impoverished racial group in the United States, with centuries of structural racism and longitudinal psychological trauma contributing to higher rates of mental illness and substance use alongside a life expectancy 5.5 years shorter than the US average 4 .…”
Section: Introductionmentioning
confidence: 99%